VITAL CHARACTERS OF PROJECT-COOPERATORS DRIVING THE SUCCESS OF CACAO PLANTATION ESTABLISHMENT IN BUKIDNON, PHILIPPINES - Vences C Valleser; Josephine L Arbes; Andrew B Melencion; Karen Debbie J Cosrojas; Glenn R Dayondon (Socio-Economics/Agribusiness Department, 2020)
One way to realize the targeted 100 thousand metric tons of dried cocoa beans by the Philippines on year 2022 is the massive establishment of new cacao plantations. With the financial support through the grant-in-aid program of the Philippine Council for Agriculture, Aquatic and Natural Resources, Research and Development, Central Mindanao University reached-out to neighboring communities and helped the people in Bukidnon, Philippines to establish new cacao plantations using the high-yielding clones recommended by the National Seed Industry Council. A total of 39 project-cooperators were involved and were provided with farm inputs as well as seminars and trainings on cacao production through the “Science and Technology Community-Based Farm (STCBF) for a Sustainable Cacao Production in Bukidnon” project. However, it cannot be denied that characters of project-cooperators have great influence on the performance of cacao plantation. This study was undertaken to determine the influence of prior learnings (previous seminars and trainings on cacao production), regularity of farm visit, involvement in farm hands-on activities and level of technology adoption of project-cooperators on the performance of established cacao plantation. Characters of project-cooperators with regard to farm management were documented during the farm monitoring and evaluation conducted by our team. Results revealed that project-cooperators who visited their farm regularly have better cacao plantation performance than those of project-cooperators who visited their farm occasionally. Apparently, cacao plantation performed better if project-cooperators were highly receptive to transferred technology. These findings can be used as guide to agricultural extension workers in Bukidnon, Philippines in the selection of project-cooperators or project beneficiaries with regard to establishment of cacao plantations.